Dynamic Active Archive Management at SDIT Al-Muddatsiriyah Jakarta - Sabrina, Mutia Eka; Mu'arif, Mu'arif; Munawwaroh, Zahrotul; Mahdi, Mahdi; Azmi, Ulul (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
Active dynamic archives are very important in an institution, namely as a memory center and presentation of information for leaders to be able to make decisions and formulate policies. To provide accurate and precise information you must have good procedures and an appropriate archive system because archives are well maintained. will be useful in the long term. This research aims to determine active dynamic archive management and the obstacles faced at SDIT Al-Muddatsiriyah Jakarta. The research method used is descriptive with a qualitative approach. The research data source consists of three informants, namely the school principal, the head of administration, and the administrative staff. This research data collection technique uses interview, observation, and documentation techniques. Data analysis was carried out using data reduction, data presentation, and conclusion. The results of this research show that active dynamic archive management consists of creating archives, using archives, maintaining archives, and depreciating archives. SDIT Al-Muddatsiriyah Jakarta has carried out archive management quite well, but there are several factors such as the borrowing stage which are not by borrowing theory. Facilities are also inadequate, and there is no special archive room. Obstacles include a lack of archivists and human resources' understanding of active dynamic archive management, inadequate retrieval of archives, and insufficient attention to archive maintenance. Efforts are being made to improve and pay attention to archive management so that not many are damaged, as well as keeping the archives well and neatly organized.